Archaeal histones: structures, stability and DNA binding. (1st April 2004) - Reeve, J.N.; Bailey, K.A.; Li, W-t.; Marc, F.; Sandman, K.; Soares, D.J.
Abstract : Structures, stability and DNA-binding properties have been established for archaeal histones from mesophiles, thermophiles and hyperthermophiles. Most archaeal histones are simply histone folds that are stabilized by dimer formation. Archaeal histones and the histone folds of the eukaryotic nucleosome core histones share a common ancestry and bind and wrap DNA similarly using conserved residues. The histone-fold residues that stabilize dimer–dimer interactions within an archaeal histone core contribute to determining archaeal histone–DNA affinity.